What happens between first symptoms and first acute exacerbation of COPD - observational study of routine data and patient survey - Alex Bottle; Alex Adamson; Xiubin Zhang; Benedict Hayhoe; Jennifer K Quint (NIHR Journals Library, 2024)
Background Chronic obstructive pulmonary disease affects nearly 400 million worldwide - over a million in the United Kingdom - and is the third leading cause of death. However, there is limited understanding of what prompts a diagnosis, how long this takes from symptom onset and the different approaches to clinical management by primary care professionals. Objectives Map out the clinical management and National Health Service contacts from symptom presentation to chronic obstructive pulmonary disease diagnosis and first acute exacerbation of chronic obstructive pulmonary disease in three time periods; construct risk prediction for first acute exacerbation of chronic obstructive pulmonary disease. Design Retrospective cohort study and cross-sectional survey. Setting Primary care. Participants Patients with incident chronic obstructive pulmonary disease aged > 35 years in England. Interventions None. Main outcome measures First acute exacerbation of chronic obstructive pulmonary disease. Data sources Clinical Practice Research Datalink Aurum; new online survey. Results Forty thousand five hundred and seventy-seven patients were diagnosed between April 2006 and March 2007 (cohort 1), 48,249 between April 2016 and March 2017 (cohort 2) and 4752 between March and August 2020 (cohort 3). The mean (standard deviation) age was 68.3 years (12.0); 47.3% were female. Around three-quarters were diagnosed in primary care, with a slight fall in cohort 3. Compliance with National Institute for Health and Care Excellence diagnostic guidelines was slightly higher in cohorts 2 and 3 for all patients; 35.8% (10.0% in the year before diagnosis) had all four elements met for all cohorts combined. Multilevel modelling showed considerable between-practice variation in spirometry. The survey on the charity website had 156 responses by chronic obstructive pulmonary disease patients. Many respondents had not heard of the condition, hoped the symptoms would go away and identified various healthcare-related barriers to earlier diagnosis. Clinical Practice Research Datalink analysis showed notable changes in post-diagnosis prescribing from cohort 1 to 2, such as increases in long-acting muscarinic antagonist (21.7-46.3%). Triple therapy rose from 2.9% in cohort 2 to 11.1% in cohort 3. Documented pulmonary rehabilitation rose from just 0.8% in cohort 1 to 13.7% in cohort 2 and 20.9% in cohort 3. For all patients combined, the median time to first acute exacerbation of chronic obstructive pulmonary disease in patients who had one was 1.4 years in cohorts 1 and 2. Acute exacerbation of chronic obstructive pulmonary disease prediction models identified some consistent predictors, such as age, deprivation, severity, comorbidities, post-diagnosis spirometry and annual review. Models without post-diagnosis general practitioner actions had a c-statistic of around 0.70; the highest c-statistic was 0.81, for cohort 2 with post-diagnosis general practitioner actions and 6-month follow-up. All models had good calibration. The three most important predictors in terms of their population attributable risks were being a current smoker and offered smoking cessation advice (32.8%), disease severity (30.6%) and deprivation (15.4%). The highest population attributable risks for variables with adjusted hazard ratios < 1 were chronic obstructive pulmonary disease review (-27.3%) and flu vaccination (-26.6%). Limitations Symptom recording and chronic obstructive pulmonary disease diagnosis vary between practice; predicted forced expiratory volume in 1 second had many missing values. Conclusions There has been some improvement over time in chronic obstructive pulmonary disease diagnosis and management, with large changes in prescribing, though patient and system barriers to further improvement exist. Data available to general practitioners cannot generate risk prediction models with sufficient accuracy. Future work It will be important to expand the COVID-era cohort with longer follow-up and augment general practitioner data for better prediction. Study registration This study is registered as Researchregistry.com: researchregistry4762. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 17/99/72) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 43. See the NIHR Funding and Awards website for further award information. Plain language summary Chronic obstructive pulmonary disease is often caused by smoking and affects over 1 million people in the United Kingdom. While there are well-established treatments, less is known on where and when patients get the diagnosis, how general practitioners investigate their symptoms and to what extent the first major flare-up ('acute exacerbation') can be predicted and prevented. Using a research database of general practitioner consultation records linked to hospital admissions and the national death register, we described patient characteristics, general practitioner actions before and following diagnosis, and, with statistical models, predictors of the first exacerbation. We looked at three time periods according to the date of diagnosis: April 2006-March 2007 (cohort 1), April 2016-March 2017 (cohort 2) and March-August 2020 (cohort 3). We sent patients a questionnaire asking about their experiences of developing symptoms, seeking medical help and getting diagnosed. We analysed records of over 70,000 patients in total. The majority were diagnosed by their general practitioner. In cohorts 2 and 3, general practitioners did the recommended tests more than in cohort 1, though in the year before diagnosis, only 10% of patients had all four done. Our survey found that many people were unaware of chronic obstructive pulmonary disease and its symptoms before their diagnosis but also that some felt they were not taken seriously by the medical team and that their diagnosis was delayed. There were improvements over time in prescribing. Most patients were offered the flu jab. Older patients, current smokers and those with other conditions such as heart failure had higher risk of an acute exacerbation. The statistical models did not perform well enough to be used to guide decision-making. Despite some improvements over time, there remain opportunities for better recognition of the condition among patients and general practitioners alike. Future work should more fully assess the impact of COVID-19. Scientific summary Background Chronic obstructive pulmonary disease (COPD) affects nearly 400 million worldwide - over a million in the UK - and is the third leading cause of death. Despite this, there is limited understanding of what prompts a diagnosis, how long this takes from symptom onset and the different approaches to clinical management taken by primary care professionals. This is particularly true regarding people with comorbidities such as asthma and heart failure (HF) that can also cause breathlessness. Objectives Map out the clinical management and NHS contacts from symptom presentation to COPD diagnosis and first acute exacerbation, acute exacerbation of chronic obstructive pulmonary disease (AECOPD) (for some patients the latter two will be the same event); investigate whether and how this varied in three cohorts since 2006; rank predictors of the first AECOPD in importance and assess whether and how this changed over time; construct and validate risk prediction models for the first AECOPD. Methods The project involved the quantitative analysis of an existing database and a new survey. The main component used the Clinical Practice Research Datalink (CPRD), which collects deidentified patient electronic health records from participating general practitioner (GP) practices; its Aurum version includes healthcare records from GP practices using EMIS® software, representing around 13% of the population in England. It includes patient-level data on demographics, tests, symptoms, diagnoses, therapies, prescriptions and referrals to secondary care. Patient-level data from these practices were linked by CPRD staff to the Office for National Statistics death register, Hospital Episode Statistics and Index of Multiple Deprivation at small area level.